Exploring mental functions utilised by male youth team-based ball-sport athletes within academy programs: a systematic review and meta-aggregation - Whitty, Joshua P.; Gray, Bon; Milne, Nikki (Frontiers in Sports and Active Living, 2024)
The rise of youth sport academies has led to a focus on long-term athletic development, and exploration into holistic approaches that incorporate psychological attributes to form biopsychosocial frameworks. The primary aim of this systematic review was to profile the psychological attributes of male youth team-based ball-sport athletes in academy-based programs and explore interactions between psychological attributes and athlete participation through the biopsychosocial model, the International Classification of Functioning, Disability and Health framework. This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Six databases; PubMed, SPORTdiscus, Proquest, PsychINFO, Embase and Scopus were searched for relevant publications from root to 14th March 2024. The search returned 3306 records, and after applying the eligibility criteria 51 studies were included at full text and were critically appraised utilising the Mixed Methods Appraisal Tool. Data synthesis revealed 178 mental functions measured across 12 ICF categories, via 66 psychometric tools. Meta-aggregation revealed mean scores for 34 mental functions across eight ICF categories and 12 sub-categories. Male youth team-based ball-sport academy athletes display high levels of orientation to self and high energy levels; moderate to high levels of motivation and self-regulation; moderate levels of psychosocial functions, conscientiousness, regulation of emotion, and organising and planning. Low levels of clinical indicators and burnout were observed. The ICF framework can be utilised as a biopsychosocial framework for sport practitioners looking to profile the multidimensional and complex attributes of team-based ball-sport youth athletes in academy programs. Systematic Review Registration:https://doi.org/10.17605/OSF.IO/9CE24.